Hubungan Leukopenia dengan Tingkat Keparahan Demam Berdarah Dengue pada Anak di RSUD Wangaya Denpasar pada Januari-Agustus 2021 - Anak Agung Ngurah Arya Yugadhyaksa; Ni Kadek Elmy Saniathi; Ni Wayan Widhidewi (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[The Correlation Between Leukopenia and The Severity of Dengue Hemorrhagic Fever in Paediatric Patients of RSUD Wangaya Denpasar from January 2021-August 2021] Dengue Hemorrhagic Fever (DHF) is one of the most concerning diseases to look out for each year especially on paediatric patients because pediatric patients are more susceptible to severe dengue infection. This is presumably because the microvasculature in children is more prone to plasma leakage. To measure the severity of DHF, a classification by World Health Organization (WHO) in 2011 is used mainly as the standards. This study aims to determine the relationship between leukopenia and the severity of dengue fever in children treated at Wangaya Regional Hospital, Denpasar. The methods this study used is an observational analytic method with cross sectional study by using medical reports as secondary data from January-August 2021 in RSUD Wangaya Denpasar. Subjects are obtained by consecutive sampling with 92 subjects. This study used chi-square analysis (x2) with 95% confidence interval (CI) and P-value of 5%. Data was analyzed using univariate and bivariate model through Statistical Package for the Social Sciences for Windows. The results of this study indicates that the number of subjects with non-shock hemorrhagic dengue fever which is 68.5% appears to be greater than subjects with shock dengue hemorrhagic fever which is 31.5%. The average leukocyte level in the subjects obtained was still in the normal range, namely 4,803 ÂµL. Chi square (x2) distribution table analysis (p=0,092), there is no significant correlation between the leukopenia with the severity of dengue hemorrhagic fever in paediatric patients of RSUD Wangaya Denpasar.